Export capabilities of the services sector in Trinidad and Tobago - a statistical assessment (UWI. Centre for International Services Cave HillBB, 2004)
Seeks to determine whether there exists a significant export market for services and what are the major services exported. Identifies the destination of these exports and their corresponding values.
Additional copy located in the Statistics Sub-Programme